Open-access vs. paywalled journals in translation and interpreting studies: is it the time to abolish stumbling blocks? - Akbari, Alireza; Shahrokhi, Mohsen (Onomázein, 2023)
The present research bibliometrically analyses the trend of free/open-accessibility of published documents in translation and interpreting (T&I) studies. To assess open-access trends, data was gathered from 106 translation-interpreting and translation-related journals from 1956 to 2020. A total of 321,964 entries (published documents) were extracted, of which 19,271 (open-access and non-open-access) entries were in the fields of T&I studies. Simply put, only 3,758 (1.16%) of entries in 106 journals were open-access (OA). This research paper used linear regression analysis to prognosticate the trend of OA in T&I studies. According to the provided regression equation, T&I paywalled journals require 53 years to fully become OA, which is indispensably regarded as a critical juncture in T&I scholarly outputs. In this light, it is time to remove any stumbling blocks through a worldly summation of open-access by translation and interpreting scholars/researchers across the globe. In the meantime, additional investigations are required to assess whether ongoing business models of publishing academic outputs foster an open-accessibility movement or impose indispensable constraints.